Coating of the NiMoO4 nanosheets on different-morphology ZnCo2O4 nanoarrays on Ni foam and their application in battery-supercapacitor hybrid devices. (June 2020) - Meng, Ya'nan; Yu, Deyang; Teng, Yifei; Qi, Hui; Liu, Xilong; Wu, Yunpeng; Zhao, Xudong; Liu, Xiaoyang
Abstract: ZnCo2 O4 @NiMoO4 core-shell nanowires (ZCNM-NW) and nanosheets (ZCNM-NS) on nickel foam (NF) were synthesized by coating NiMoO4 nanosheets on different ZnCo2 O4 nanostructures via facile hydrothermal reactions, followed by a calcination process. The synthesized materials were tested as the working electrodes in a three-electrode configuration. By comparing the performances of these electrodes, it was found that both of the ZCNM-NW and ZCNM-NS electrodes exhibited enhanced electrochemical performance and excellent cycling stability, of which the ZCNM-NS delivered an extraordinary specific capacity as high as 1158.0 C g −1 at a current density of 10 mA cm −2, and retained 103.4% of the initial specific capacity after 5000 cycles. To further investigate the electrochemical performance of the prepared electrode, a battery-supercapacitor hybrid (BSH) device was assembled with the prepared ZCNM-NS electrode as the positive electrode and activated carbon (AC) as the negative electrode in 2 M KOH, which showed a high energy density of 25.3 W h kg −1 at a power density of 787.9 W kg −1 and 18.4 W h kg −1 at a power density of 9467.5 W kg −1 . These remarkable electrochemical performances suggest that the as-synthesized ZCNM-NS had a great potential for advanced electrodes of BSH devices.